Enhancing student practical skills using the modified flipped classroom (MFC) approach / Prasanna Ramakrisnan - Ramakrisnan, Prasanna (UiTM Press, 2024)
This research aimed to investigate the effectiveness of a modified flipped classroom (MFC) approach in enhancing multimedia practical skills among undergraduate students. Traditional flipped classroom approaches were merged with learning contents created and shared with students prior to the classroom time; and classroom hands-on sessions tailored for multimedia skill acquisition. In the MFC approach, the classroom time is converted to synchronous online classes and problem-solving activities. A cohort of 42 undergraduate students enrolled in a multimedia computing course was divided into two groups: a control group (21) receiving traditional lectures and lab sessions, and an experimental group (21 students) exposed to the modified flipped classroom approach. The study spanned 14 weeks, with pre and post-assessments used to evaluate students’ practical skills using assignment evaluations. The effectiveness of the modified flipped classroom approach was based on two indicators (i) the student’s assignment performance and (ii) the student’s learning experience. The experimental group demonstrated an improvement in multimedia practical skills compared to the control group. There was an 8.25% increase in students’ performance in designing, develop, and implementing multimedia assignments. Quantitative learning experience feedback indicated that students in the modified flipped classroom liked the approach and helped to understanding of the content and practical approach better. Implementing a modified flipped classroom approach not only prepares students for the professional world but also accommodates diverse learning styles, promoting holistic learning and pratical skill development in the multimedia domain.